Digital atlas of the zebra finch (Taeniopygia guttata) brain: A high‐resolution photo atlas. Issue 16 (25th September 2013) - Karten, Harvey J.; Brzozowska‐Prechtl, Agnieszka; Lovell, Peter V.; Tang, Daniel D.; Mello, Claudio V.; Wang, Haibin; Mitra, Partha P.
ABSTRACT We describe a set of new comprehensive, high‐quality, high‐resolution digital images of histological sections from the brain of male zebra finches (Taeniopygia guttata) and make them publicly available through an interactive website (http://zebrafinch.brainarchitecture.org/). These images provide a basis for the production of a dimensionally accurate and detailed digital nonstereotaxic atlas. Nissl‐ and myelin‐stained brain sections are provided in the transverse, sagittal, and horizontal planes, with the transverse plane approximating the more traditional Frankfurt plane. In addition, a separate set of brain sections in this same plane is stained for tyrosine hydroxylase, revealing the distribution of catecholaminergic neurons (dopaminergic, noradrenergic, and adrenergic) in the songbird brain. For a subset of sagittal sections we also prepared a corresponding set of drawings, defining and annotating various nuclei, fields, and fiber tracts that are visible under Nissl and myelin staining. This atlas of the zebra finch brain is expected to become an important tool for birdsong research and comparative studies of brain organization and evolution. J. Comp. Neurol. 521:3702–3715, 2013. © 2013 Wiley Periodicals, Inc.